Analysis and modelling of longitudinal deformation profiles of tunnels excavated in strain-softening time-dependent rock masses. (September 2020) - Song, Fei; Rodriguez-Dono, Alfonso; Olivella, Sebastia; Zhong, Zhen
Abstract: Rock mass behaviour model selection, in particular, to represent the post-failure behaviour and time-dependent behaviour of rock masses, are critical issues in the correct application of tunnelling design techniques such as the convergence-confinement method or numerical modelling. This study provides a general numerical approach for predicting longitudinal deformation profiles using a coupled ViscoElastic-ViscoPlastic Strain-Softening (VEVP-SS) model. A viscous dashpot and the strain-softening model are coupled to simulate the progressive damage process and creep failure behaviour of rock masses. Different failure criteria are considered to simulate the post-failure behaviour. As a verification step, numerical creep tests are carried out to analyse the coupled behaviour, and the basic viscoelastic and strain-softening results of the VEVP-SS model are compared with analytical solutions and numerical results. The proposed method is able to consider the coupling between post-failure behaviour and time-dependent behaviour, thus providing a new alternative method for preliminary tunnel design. Parametric analyses are then carried out to investigate the influence of different aspects on the longitudinal deformation profiles. The tunnel deformation based on the VEVP-SS model is larger than the corresponding elastic–plastic results due to the contribution of the creep behaviour, and the excavation rate becomes relevant when considering time-dependent behaviour.